Analisis Faktor-Faktor yang Mempengaruhi Underpricing pada Penawaran Umum Perdana - Novita Indrawati (Jurnal Akuntansi dan Bisnis, 2005)
The objectives of this study are to obtain empirical evidence and test the factors that affect underpricing of Initial Public Offerings. The factors are proceeds, size, age, percentage of share offered, profitability, leverage, and market condition (IHSG). This study was carried out on the company that conduct Initial Public Offerings in period of 2000-2002 at Jakarta Stock Exchange, with two types of sample: 56 underpricing firms and total of sample of 67 firms as comparison. I use multiple regression analysis to test the hyphotesis. The results of this study indicate that size and leverage affected underpricing. But, other factors: age, percentage of share offered, profitability, and market condition did not affect underpricing.